The Effect of Displacement Mode of Rigid Retaining Walls on Shearing Bands by Active Earth Pressure - Sekkel, A.; Meghachou, M. (Engineering, Technology & Applied Science Research, 2013)
This work treats the physical modeling of failure mechanisms by active earth pressure. This last is developed by retaining wall movement. A lot of research showed that wall displacement has a significant effect on active earth pressure. A good comprehension of active earth pressure phenomenon and its failure mechanisms help us to better conceive retaining walls. The conception of a small-scale model allowed the realization of active earth pressure tests, while displacing the mobile wall toward the outside of the massif. The studied material is that of Schneebeli; light two-dimensional material made of cylindrical plastic rollers, simulating granular non-cohesive soil. The evolution of shearing zones under continuous and discontinuous displacement modes of mobile walls by correlation pictures allows the investigation of the localization of deformations and failure mechanisms.